Effect of sacrificial fiber length on gas permeability of lanthanum carbide. Issue 4 (March 2018) - Corradetti, S.; Anelli, C.; Biasetto, L.; Innocentini, M.D.M.; Carturan, S.; Colombo, P.; Andrighetto, A.
Abstract: Lanthanum carbide is considered as a potential target for generation of radioactive ion beams by means of the ISOL ( Isotope Separation On Line ) technique. This method requires the use of porous refractories as targets, in order to work in extreme conditions (more than 2000 °C in high vacuum) to enhance the release of the generated isotopes. Several techniques can be used to generate open interconnected porosity in lanthanum carbide. The use of polymeric (nylon and polypropylene) fibers as sacrificial fillers was successfully tested in a previous work. Here, the effect of the fibers length is reported and discussed in terms of porosity and permeability.